2018
DOI: 10.1109/led.2018.2856920
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of Al2O3/H-Diamond MOSFETs Utilizing Vacuum Annealing and V2O5 as a Surface Electron Acceptor

Abstract: We report on the performance enhancement of 250 nm gate-length H-diamond FETs through thermal treatment of devices at 400°C and the incorporation of V2O5 as a surface electron acceptor layer. Encapsulation of the H-diamond surface with V2O5 is found to increase the transfer doping efficiency and reduce device access resistance. A reduction in ohmic contact resistance and channel resistance beneath the gate after thermal treatment at 400°C was found to further reduce device onresistance and increase the maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
1
6
1
Order By: Relevance
“…In this instance, V th is more representative of the ON-OFF ratio for smaller devices that do not pinch-off. These values are relatively in close agreement for a V 2 O 5 -doped MOSFET with L g of 250 nm, reported here [17]. While the substrate for this MOSFET exhibited lower sheet resistance, ON-resistance was notably higher due to increased contact and access resistance.…”
Section: Table I Summary Of Extracted Parameters For Each Gate Lengthsupporting
confidence: 89%
See 1 more Smart Citation
“…In this instance, V th is more representative of the ON-OFF ratio for smaller devices that do not pinch-off. These values are relatively in close agreement for a V 2 O 5 -doped MOSFET with L g of 250 nm, reported here [17]. While the substrate for this MOSFET exhibited lower sheet resistance, ON-resistance was notably higher due to increased contact and access resistance.…”
Section: Table I Summary Of Extracted Parameters For Each Gate Lengthsupporting
confidence: 89%
“…OFF-state performance significantly worsens as the small gate length struggles to modulate the high current. These values for drain current are substantially higher than those reported elsewhere for a diamond V 2 O 5 FET [17], [20], [21]. Both I d saturation and channel pinch-off could not be achieved prior to gate failure.…”
Section: Table I Summary Of Extracted Parameters For Each Gate Lengthcontrasting
confidence: 63%
“…The |I DSmax | for the novel triple-gate fin-type MOSFET was 271.3 mA mm −1 at an average L G of 3.3 µm. Recently, there have been new developments for the fabrication of high current output H-diamond MOSFETs [29], [30]. It has been reported that when the entire surface of the H-diamond channel is covered by a V 2 O 5 film, the |I DSmax | values for the V 2 O 5 /H-diamond type MOSFETs are as high as 280.0 and 375.0 mA mm −1 at an L G of 2.0 and 0.25 µm, respectively [29], [30].…”
Section: Resultsmentioning
confidence: 99%
“…Both of these results have proven difficult to reproduce, though several groups have reported drain currents ≤0.6 A mm −1 using air transfer doping which is known to be unstable with temperature and time, an example of which is shown in Figure . Macdonald, Verona, and Tordjman using transition metal oxides have demonstrated lower resistances, 1.5 to 4 kΩ sq −1 , than most Al 2 O 3 ‐capped diamond, 4 to 12 kΩ sq −1 , but have not yet been able to fabricate MISFETs with drain currents >0.4 A mm −1 . This could be the result of the transition metal oxides changing their valence state under the high electric fields generated in a MISFET, mobile ions in the oxide layer, or just device fabrication issues.…”
Section: Discussionmentioning
confidence: 99%